O relato de si em João Vêncio: os seus amores, de Luandino Vieira – do narrador à sociedade luandense - Melchiades, Aline Souza (2021)
This dissertation aims to carry out a study about the self-narrative performed by the protagonist and character narrator of the novel João Vêncio: seus amores, written in 1968 and published in 1979, whose authorship is from the Portuguese-Angolan writer José Luandino Vieira. According to Butler (2017), the subject cannot narrate himself without taking certain responsibility for the social conditions in which he arises. In this sense, we highlight the narrator's repporting as an analytical category capable of resignifying the social plan, subverting and decolonizing the oppression and violence brought about by the colonial system, in the Angolan scenario. Our references for this work are Chaves (2005), who broadly discusses colonial experience and literary territories; Hamilton (1999), who depicts the Palop literature; Tutikian (2006) and Hall (2005), both analyzing the question of identity; Santos (2009), who positions himself about the discourse between narrator and narratee; Macêdo (2002, 2004) discussing the conception of “pretoguês” and the theme of the geography of Luanda in Angolan fictions; Butler (2017), who brings a social approach to self-reporting; Mignolo (2017), who brings a decolonial perspective and Candau (2011), relating memory and identity; Halbwacks (1990) discussing individual and collective memory; Kilomba (2019), addressing the issue of the double alterity of black women as a consequence of the oppression of the colonial system; Foucault (1999), discussing the surveillance of institutions and the representation of the Panopticon; Bourdieu (2012), considering the idea of virility as a representation of male domination; (MERUJE; ROSA, 2013), discussing the conception of the sacrificial rite elucidated by Girard (1979); Torres (2009), reflecting on the issues of colonization of being, knowledge and power; Fanon (1997 and 2008), discussing the colonial conscience and the recognition of the former subject, inserted in this oppressive system; Mbembe (2001, 2018), discussing the tendency of African literary productions to reinvent or re-signify the traditions of the African universe and the racial issue, in the psychological scope of former subjects; Žižec (2014), arguing about subjective and objective violence, which we associate in our study with the marks of the dominant and oppressive colonial system.